12-6x=2x+10

Simple and best practice solution for 12-6x=2x+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-6x=2x+10 equation:


Simplifying
12 + -6x = 2x + 10

Reorder the terms:
12 + -6x = 10 + 2x

Solving
12 + -6x = 10 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
12 + -6x + -2x = 10 + 2x + -2x

Combine like terms: -6x + -2x = -8x
12 + -8x = 10 + 2x + -2x

Combine like terms: 2x + -2x = 0
12 + -8x = 10 + 0
12 + -8x = 10

Add '-12' to each side of the equation.
12 + -12 + -8x = 10 + -12

Combine like terms: 12 + -12 = 0
0 + -8x = 10 + -12
-8x = 10 + -12

Combine like terms: 10 + -12 = -2
-8x = -2

Divide each side by '-8'.
x = 0.25

Simplifying
x = 0.25

See similar equations:

| 11x+32=56 | | 3x-4=-x+6 | | U=5(6n+31)+9(n+1) | | 7x-2=3x-22 | | 40x+70y=6000 | | 3w+4=5m+7-m | | X+3x+2y= | | 2(3-x)+7=2x-(x-4) | | 6x+12=12x+6 | | 0.5x+1=2.5x | | 4y-5x=60 | | 8z=2xb | | 12=2(x-4)-6 | | 2(3-x)+7=2x-4(x-4) | | 3(h+4)+5=35 | | (1+x)(1+z)= | | 10x^2+1210=0 | | 2ydx-2xdy=0 | | 18i-14i= | | 5x+-6+2=7x+-6 | | .6k-(k+.25)=.05(k+1) | | Z-4z=9z-9-z | | 2(5-2v)=5(v-5) | | 87-n=13 | | 24n^3+30n^2=0 | | -21a+28a-6=10 | | 4[(12+5)-1024]= | | 5y-15+6=5y+8-1x+17 | | 4x^2+6x+1=2x^2+6x-6+1 | | 8p+5-3=9+7p | | 3(d-2)=15 | | 3s+5w=19 |

Equations solver categories